1 + 2 0 1 4 1 + 2 0 1 5 1 + 2 0 1 6 1 + 2 0 1 7 × 2 0 1 9 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Tanishq Varshney Nice problem.
( x + n ) 2 = x 2 + 2 x n + n 2 = x 2 + n ( x + ( x + n ) )
We can continue with this method , but it'll have a limited scope , so to cover a whole new level of possible expressions , let's introduce a new variable k into the expression .
x + n = x 2 + n ( x − k + ( x + ( n + k ) ) ) = x 2 + n ( x − k + x 2 + ( n + k ) ⋅ ( x − k + x 2 + ( n + 2 k ) ⋅ ( x − k + …
Now , we just have to set the values of n=2014 and x=1 .
Hence , the L.H.S becomes 1+2014 = 2015 .
Earlier I used to be terrified and used to hate solving such questions(no offense Tanishq!) but ever since I learnt this method , I have been in a position to solve almost all questions of this type ;)
Problem Loading...
Note Loading...
Set Loading...
We note that: 1 + ( n − 1 ) ( n + 1 ) = 1 + n 2 − 1 = n 2 = n .
Therefore, we have:
1 + 2 0 1 4 1 + 2 0 1 5 1 + 2 0 1 6 1 + 2 0 1 7 × 2 0 1 9 = 1 + 2 0 1 4 1 + 2 0 1 5 1 + 2 0 1 6 × 2 0 1 8 = 1 + 2 0 1 4 1 + 2 0 1 5 × 2 0 1 7 = 1 + 2 0 1 4 × 2 0 1 6 = 2 0 1 5